2013
DOI: 10.4021/jocmr879w
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin and Radicular Pain Study (PARPS) for Cervical Spondylosis in a Multiracial Asian Population

Abstract: BackgroundPain from cervical spondylosis (CS) may result from degenerative spinal canal stenosis (cervical spondylotic myelopathy (CSM)) or lateral recesses compromise, leading to nerve root compression (cervical spondylotic radiculopathy (CSR)). Pregabalin was shown to be effective in randomized, placebo-controlled trials for post-herpetic neuralgia and diabetic neuropathy. We evaluate its efficacy in CS with underlying CSR or CSM in a prospective study comprising Asian patients for the first time.MethodsPati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In the present observational study of Japanese patients with chronic refractory cervical pain with a NeP component, significant improvements in self-reported sleep interference and pain scores were reported after 8 weeks of treatment with pregabalin (with or without other analgesics) compared with “usual care” with conventional analgesic therapy. In addition to supporting evidence for pregabalin improving aspects of sleep, the data presented here support the efficacy of pregabalin in other patients with neck pain,2931,39 and in Japanese patients with different types of NeP, based on clinical trial data,21,22,40 as well as non-interventional24 and long-term open-label studies for postherpetic neuralgia, diabetic peripheral neuropathy26,41 and central NeP 27. The reductions in PRSIS (–1.17) and pain NRS (–2.26) in the current study were similar to those reported previously in a similarly designed study of Japanese patients treated with pregabalin for chronic lower back pain associated with NeP 24.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present observational study of Japanese patients with chronic refractory cervical pain with a NeP component, significant improvements in self-reported sleep interference and pain scores were reported after 8 weeks of treatment with pregabalin (with or without other analgesics) compared with “usual care” with conventional analgesic therapy. In addition to supporting evidence for pregabalin improving aspects of sleep, the data presented here support the efficacy of pregabalin in other patients with neck pain,2931,39 and in Japanese patients with different types of NeP, based on clinical trial data,21,22,40 as well as non-interventional24 and long-term open-label studies for postherpetic neuralgia, diabetic peripheral neuropathy26,41 and central NeP 27. The reductions in PRSIS (–1.17) and pain NRS (–2.26) in the current study were similar to those reported previously in a similarly designed study of Japanese patients treated with pregabalin for chronic lower back pain associated with NeP 24.…”
Section: Discussionsupporting
confidence: 78%
“…One study of acute sciatica in Australian patients suggests pregabalin is not effective at reducing acute pain,45 nor in other types of lumbar radial pain 46. Whereas other studies have demonstrated the efficacy of pregabalin, in combination with other agents, in NeP associated with nerve compression,31,39 including one small study of chronic sciatica in Australian patients 46. These observations collectively highlight the complexity of NeP, and the need for more high-quality studies to confirm the efficacy of specific drug combinations in different patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of pregabalin has been demonstrated in multiple randomized, controlled trials for a number of neuropathic pain conditions such as post-herpetic neuralgia ( 16 , 17 ), diabetic neuropathy ( 18 , 19 ), fibromyalgia ( 20 ), and spinal cord injury pain ( 15 ). We encountered two previous studies of pregabalin use in patients with RP ( 21 , 22 ). While one such trial reported inconclusive results ( 21 ), the other reported the efficacy of pregabalin in patients with cervical radiculopathy ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…We encountered two previous studies of pregabalin use in patients with RP ( 21 , 22 ). While one such trial reported inconclusive results ( 21 ), the other reported the efficacy of pregabalin in patients with cervical radiculopathy ( 22 ). The latter trial, however, cited significant study limitations and recommended further evaluation of pregabalin in patients with RP by a well-designed study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Ye et al [10]. observed the clinical efficacy of percutaneous full-endoscopic cervical foraminotomy in the treatment of bony stenosis of the intervertebral foramen, indicating that it is a safe and feasible surgical approach [11]. This study aimed to evaluate and measure the effect of decompression, as well as evaluate the clinical efficacy of percutaneous full-endoscopic cervical foraminotomy in the treatment of bony stenosis of the cervical nerve root canal.…”
Section: Introductionmentioning
confidence: 98%